Lead and Cadmium Content of Total Suspended Particulates in the Atmosphere over the Klang Valley - Hashim, Jamal Hisham; Hashim, Zailina (Universiti Putra Malaysia Press, 1995)
Five sites (urban, suburban, new township, industrial, and rural) were selected and sampled for total suspended particulates (TSP) using high-volume samplers. The TSP were then analysed for their lead and cadmium content in 3 extraction fractions. While the most polluted sites for atmospheric lead and cadmium were different, namely the BBP (Pudu Fire Station) urban and UPM (Universiti Pertanian Malaysia) suburban sites, respectively, the least polluted site was the same for both metals, namely the KSM (Sungai Merab Village) rural site. Comparisons of the temporal distribution patterns of TSP, lead and cadmium indicate that variation in TSP concentrations does not seem to influence variations in lead and cadmium concentrations. Analysis of fractionation patterns suggests that the BBP urban site has slightly higher percentages of anthropogenic lead and cadmium from fresh sources than the other sites.